2023
DOI: 10.1021/acs.orglett.2c04292
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-Phenolate Exchange as a Mild, Fast, and High-Yielding Method toward the Synthesis of Sulfonamides

Abstract: Sulfonamides have many important biological applications, yet their synthesis often involves long reaction times under dry and non-ambient conditions. Here we report the synthesis of a large range of sulfonamides at room temperature using 4-nitrophenyl benzylsulfonate as a starting material. Sulfonamides were prepared from a wide range of aliphatic, linear, and cyclic amines, anilines, and N -methylanilines. The yields and reaction times observed here were comparable to or better than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In this, we noted the potential of enantiospecific S­(VI) exchange reactions . Such reactions, like the sulfur–fluorine exchange (SuFEx) and sulfur–phenolate exchange (Su­Phen­Ex) click reactions, have become widely popular tools in synthetic chemistry for the synthesis of both small molecules, , biologically relevant molecules, , and new functional organic materials . Importantly, these reactions are highly efficient, resulting in high yields of the desired product, and they are often performed under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this, we noted the potential of enantiospecific S­(VI) exchange reactions . Such reactions, like the sulfur–fluorine exchange (SuFEx) and sulfur–phenolate exchange (Su­Phen­Ex) click reactions, have become widely popular tools in synthetic chemistry for the synthesis of both small molecules, , biologically relevant molecules, , and new functional organic materials . Importantly, these reactions are highly efficient, resulting in high yields of the desired product, and they are often performed under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these reactions are highly efficient, resulting in high yields of the desired product, and they are often performed under mild conditions. Our research group has shown a keen interest in the area of sulfur­(VI) exchange reactions, specifically as a tool to introduce intrinsically chiral click chemistries. , Using the enantiospecificity observed for small-molecule SuFEx and SuPhenEx reactions of chiral sulfonimidoyl fluorides and phenolates, , our group synthesized, for example, configurationally chiral polymers using disulfonimidoyl fluorides (further: di-SFs) and diphenols (Figure ). Interestingly, in nearly all polymerization reactions byproducts were observed in low yields (typically <5%) with a distinct mass that could be directly related to the structure of the di-SFs and diphenolates used.…”
Section: Introductionmentioning
confidence: 99%